Effect of syngas moisture content on the emissions of micro-gas turbine fueled with syngas/LPG in dual fuel mode - Sadig, H. (EDP Sciences, 2014)
Syngas produced by gasification has a potential to be one of the fueling solutions for gas turbines in the future. In addition to the combustible constituents and inert gases, syngas derived by gasification contains a considerable amount of water vapor which effect on syngas combustion behaviour. In this work, a micro-gas turbine with a thermal capacity of 50 kW was simulated using ASPEN Plus. The micro gas turbine system emissions were characterized using dry syngas fuels with a different composition, syngas 1 (10.53 H 2, 24.94 CO, 2.03 CH4, 12.80 CO2, and 49.70 N2) and syngas 2 (21.62 H2, 32.48 CO, 3.72 CH 4, 19.69 CO2, and 22.49 N2) mixed with LPG in a dual fueling mode. The effect of syngas moisture content was then studied by testing the system with moist syngas/LPG with a moisture content ranging from 0 to 20 by volume. The study demonstrates that the syngas moisture content has high influence on nitrogen oxides and carbon monoxide emissions. It's found that for 5 syngas moisture content, the NOx emission were reduced by 75.5 and 83 for Syngas 1 and Syngas 2 respectively. On carbon monoxide emissions and for same moisture content ratio, the reduction was found to be 43 and 57 for syngas1 and syngas 2 respectively. Â© 2014 Owned by the authors, published by EDP Sciences.